Peran Vital Guru dalam Konsep Pendidikan Islam (Peran Guru didalam Pendidikan Pondok Modern Darussalam Gontor) - Muthmainnah Choliq; Dzikriyah Lailatul Rohmah; Fanisa Aulia Putri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
In a broad sense teacher is a professional whose job is to impart knowledge, which can include various titles such as Qur’an teacher, dance teacher, sports teacher, and etc. A teacher is someone who provides the spiritual soul or knowledge, moral education and etc.  The teacher has a higher position because he is a spiritual father who provides knowledge, guides morals, and rectify behavior’s students. Teachers must have duties that are carried out according to the Islamic perspective as well as the Quran. A teacher must have an important role that makes them more grown-up. There are three vital roles of teachers: personal, professional, and social.   Inside PMDG, the role of teachers is one of the important elements when it comes to teaching and learning activities. Because a teacher at PMDG in addition to being a teacher, they also become an educator.  It can be seen from the personality of a teacher, the professionalism of a teacher in teaching, and also the social action perceived by the teachers while teaching there. Actually, the teacher who teaches his students is teaching themselves, and the teacher who educates his students is educating himself. For that matter, the importance of educating and teaching has a highest position in Islam.